Characteristics of Reported Deaths Among Fully Vaccinated Persons With Coronavirus Disease 2019—United States, January–April 2021. (29th January 2022) - François Watkins, Louise K; Mitruka, Kiren; Dorough, Layne; Bressler, Sara S; Kugeler, Kiersten J; Sadigh, Katrin S; Birhane, Meseret G; Nolen, Leisha D; Fischer, Marc
Abstract: Background: Vaccines against coronavirus disease 2019 (COVID-19) are highly efficacious, but severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections do occur after vaccination. We characterized COVID-19 cases among fully vaccinated persons with an outcome of death. Methods: We analyzed COVID-19 cases voluntarily reported to the Centers for Disease Control and Prevention by US health departments from 1 January to 30 April 2021. We included cases among US residents with a positive SARS-CoV-2 test result ≥14 days after completion of an authorized primary vaccine series and who had a known outcome (alive or dead) as of 31 May 2021. When available, specimens were sequenced for viral lineage and death certificates were reviewed for cause(s) of death. Results: Of 8084 fully vaccinated persons with reported COVID-19 during the surveillance period, 245 (3.0%) died. Compared with patients who remained alive, those who died were older (median age, 82 vs 57 years;), more likely to reside in a long-term care facility (51% vs 18%), and more likely to have ≥1 underlying health condition associated with risk for severe disease (64% vs 24%) (all P  < .01). Among 245 deaths, 191 (78%) were classified as COVID-19 related. Of 106 deaths with available death certificates, COVID-19 was listed for 81 deaths (77%). There were no differences in the type of vaccine administered or the most common viral lineage (B.1.1.7). Conclusions: COVID-19 deaths are rare in fully vaccinated persons, occurring most commonly in those with risk factors for severe disease, including older age and underlying health conditions. All eligible persons should be fully vaccinated against COVID-19 and follow other prevention measures to mitigate exposure risk. Abstract : Deaths among persons fully vaccinated against coronavirus disease 2019 (COVID-19) were rare and occurred most commonly among those with risk factors for severe COVID-19, including older age and underlying health conditions. Most deaths were COVID-19 related.